Exploring the influence of breastfeeding on abdominal adiposity in young children using the waist to height ratio. Issue 2 (4th June 2013) - Nambiar, Smita; Truby, Helen; Davies, Peter S.W.
Abstract: Aim: The aim of the present study was to investigate the association between the duration of predominant breastfeeding and the waist to height ratio—a validated index of abdominal adiposity. Methods: Waist to height ratio (waist circumference/height, both in centimetres) and body mass index (weight (kg)/height (m 2 ) ) were collected from 896 children aged 5.00–7.99 years. Mothers of these children reported on early feeding behaviour and indicated their highest level of education attained. The 75th and 95th percentiles were used to define high and very high waist to height ratio. Overweight and obesity defined by body mass index were also included in the analyses. Results: There were a higher proportion of children ≥75th percentile for waist to height ratio among the never breastfed group compared to breastfed children. This was statistically significant only in females ( P = 0.002). Females predominantly breastfed for 4–6 months ( P = 0.003) and >12 months ( P = 0.006) had significantly lower mean waist to height ratio than those never breastfed. A similar pattern emerged with body mass index. Among males, delaying solids for ≥6 months was associated with significant decreases in waist to height ratio and body mass index. Females were six times more likely to have waist to height ratio ≥95th percentile than children predominantly breastfed for 4–6 months. This was statistically significant. Increasing maternal education was related to breastfeeding duration. Conclusion: Prevalence of overweight and high abdominal adiposity was significantly greater among females who were never breastfed. Females who were predominantly breastfed for at least 4–6 months had the lowest mean waist to height ratio and body mass index and also the greatest reduction in the risk of very high waist to height ratios.